Suitability Analysis of Office Building Design against Maintenance Cost (Case Study of Serayu Opak River Basin Organization, Yogyakarta Province) - Mario Puji Hersanto; Ashar Saputra; Suprapto Siswosukarto (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2017)
This study aims to determine the effect of building design's inaccuracy against the cost of maintenance, by taking the research in Serayu Opak River Basin Organization, Water Resources Field and Water Resources Management Center in Yogyakarta Special Region. The first step is to analyze the inaccuracy of building design based on the result of interview and observation during field survey. The second step is to analyze the cost of building maintenance. The third step is to analyze the maintenance costs used to minimize the effects of the inaccurate design of the building. The result shows the inaccuracy of building design in the form of the use of clear glass without coated glass film and the absence of heat insulator on the roof of the building cause the room to become hot. The installation of rain gutters without vertical pipes, toilet facilities in the entire building is not yet complete, inadequate accessibility for persons with disabilities, and inadequate corridor design. There is a small portion of the maintenance budget used for reducing the impact of building design's inaccuracy, so it can be concluded that the design of the building is less meet the requirements of the Government regulations.